2018
DOI: 10.1167/iovs.18-24758
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Contact Lens Discomfort With Anti-Inflammatory Approaches: A Randomized Controlled Trial

Abstract: CLD was attenuated by oral long-chain omega-3 supplementation for 12 weeks. Acute (2 week) topical corticosteroids and longer-term (12 week) omega-3 supplementation reduced tear levels of the proinflammatory cytokines IL-17A and IL-6, demonstrating parallels in modulating ocular inflammation with these approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 52 publications
0
30
1
Order By: Relevance
“…However, as other studies have shown that the beneficial effects of using eye drops may not manifest until several months following treatment [233], it may be that the two-week length of the trial was insufficient to see any potential effects. A three month trial of a topical drop omega-3 formulation (Remogen Omega; TRB Chemedica International SA, Vouvry, Switzerland) (marketed as a non-preserved lubricant) found no significant change in CLEDQ-8 or NISDT (termed noninvasive tear film stability on the contact lens surface) score compared to participants orally ingesting a placebo [235].…”
Section: Rewetting Dropsmentioning
confidence: 99%
“…However, as other studies have shown that the beneficial effects of using eye drops may not manifest until several months following treatment [233], it may be that the two-week length of the trial was insufficient to see any potential effects. A three month trial of a topical drop omega-3 formulation (Remogen Omega; TRB Chemedica International SA, Vouvry, Switzerland) (marketed as a non-preserved lubricant) found no significant change in CLEDQ-8 or NISDT (termed noninvasive tear film stability on the contact lens surface) score compared to participants orally ingesting a placebo [235].…”
Section: Rewetting Dropsmentioning
confidence: 99%
“…Lid hygiene such as warm compresses and lid scrubs [380], commercial eyelid wipes [453], warming masks [471] and microblepharon exfoliation of the eyelids [472], as well as a liposomal spray when applied to the upper eyelids [428] have also shown varying degrees of success for improving symptoms of CLD. Furthermore, oral supplementation with fish oil also improved comfort [468].…”
Section: Managementmentioning
confidence: 95%
“…Numerous management options for CLD are available. The mainstay of treatment options are rewetting drops including saline [461,462], hypo-osmotic saline [463], aqueous-based [362,462,[464][465][466], lipid-based [362,419,465,467,468] and povidone [453] eye drops. Increasingly, eye drops with anti-inflammatory properties including Manuka honey [464] and lifitigrast 5% [469] instilled twice daily (before and after lens wear) and 2% rebamipide [470] instilled four times daily with contact lenses in situ, are being utilised.…”
Section: Managementmentioning
confidence: 99%
“…Benefits to tear film stability, increased tear secretion and a reduction in DED symptoms have been noted with short‐term consumption, as little as 30 days . Contact lens discomfort as well as interleukin‐17 and interleukin‐6 levels have also been shown to be decreased with oral and topical omega‐3 supplementation, at a level comparable to that effected by topical corticosteroid use . While the balance of evidence is in favour of benefits from omega‐3 supplementation, a year‐long supplementation with a fish‐derived omega‐3 was found to show no significant difference in symptoms of DED according to the ocular surface disease index score relative to a high‐dose olive oil placebo, and more studies evaluating the optimal dosage and duration of treatment from interventions for dry eye, based on the anti‐inflammatory effects of omega‐3, are warranted …”
Section: Effect Of Treatments For Dry Eye Diseasementioning
confidence: 99%